Business contingency, strategy formation, and firm performance: An empirical study of Chinese apparel SMEs - Ting Chi (Administrative Sciences, 2015)
This study empirically investigated how small and medium-sized Chinese apparel enterprises (SME) formed their strategy as a response to the characteristics of business environment in order to achieve competitive business performance. An environment-strategy-performance model was proposed and tested. Using primary data gathered by a questionnaire survey of the Chinese apparel industry, factor analysis and structural equation modeling (SEM) were conducted for measurement and structural model analysis and hypothesis testing. Results show the proposed model met parsimonious statistical criteria. The differences in strategy responses to environment between high- and low-performing firms were striking. Confronting an increasingly turbulent business environment, high performers emphasized differentiation strategy through higher quality, better delivery performance, and greater flexibility than cost reduction. In contrast, low performers prioritized low cost while quality and flexibility were given certain weights. The lack of clear focus on strategies could result in a relatively lower performance. While the process of government-led industrial upgrading continues, forward-looking firms have proactively shifted their strategic focus from solely or mainly cost reduction to a variety of differentiating factors which bring in added value and are less imitable by competitors.
Keywords: 350; business contingency; SMEs; firm performance; strategy formation